The dynamics of firm creation fuelled by higher education institutions within innovation networks - Simões, J. (2015)
This research considers the factors that contribute to venture creation, through the use of innovation networks, within state-owned higher education institutions (HEIs) in Portugal. The paper reviews the literature on current approaches to firm creation through models of innovation networks and analyses data collected through a questionnaire completed by 255 nascent entrepreneurs who, at one level or another, had attended HEIs with the specific purpose of developing their entrepreneurial skills. The data was submitted to factor analysis and a logistic regression model. The results show that the cooperation and development of relationships with other agents in the innovation network is the main route by which HEIs stimulate firm creation